Dynamic modeling of dielectric elastomer actuators with a minimum energy structure. (23rd July 2019) - Zou, Jiang; Gu, Guoying
Abstract: Dielectric elastomer actuators with a minimum energy structure (DEAs-MES) have been widely used in developing different soft robotics, owing to their large strain and simple structure. However, there is rare study on dynamic modeling of DEAs-MES because of both geometric and viscoelastic nonlinearities. In this work, we present a dynamic modeling approach for DEAs-MES by using an equivalent slider-crank mechanism, where geometric nonlinearity is simplified for calculating the stress distribution on DEAs-MES and the viscoelastic nonlinearity is represented by a series of viscoelastic units. In this sense, the Lagrange equation can be utilized to obtain the analytical dynamic model of DEAs-MES. The quantitative comparisons between experimental data and predicted results well demonstrate the effectiveness of the development, where the maximum root-mean-square errors are less than 10.78%. This work presents the early attempt to analytically characterize the dynamic response of DEAs-MES, which will be necessary for further dynamic-model based control design in the field of soft robotics.